IMPLEMENTASI PENGELOLAAN DANA DESA DI KABUPATEN HULU SUNGAI UTARA PROVINSI KALIMANTAN SELATAN - Tumija Tumija; Riska Julianti (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT This study aims to describe the implementation and administration in the management of the Village Fund fiscal year 2016, along with the a limiting factor in the management and government’s efforts to overcome these obstacles. This research was conducted at the Community Empowerment Body and village authorities who have changed to the Department of Community Empowerment and Village (DPMD) and take six villages as samples in Hulu Sungai Utara, namely Cempaka, Kalintamui, Galagah Hulu, Kandang Halang, Pangkalan Sari and Benua Hanyar. This research uses descriptive qualitative method with inductive approach. Data collection techniques obtained by carrying out observations, interviews and documentation. While the data analysis techniques that are redaction Data reduction, Data display, Conclusion drawing. The results showed that the implementation and Administration of Village Funds in North Hulu Sungai Regency in principle have been done based on Regulation of Regent of Hulu Sungai Utara number 11 year 2016, specially on three sample villages of Cempaka Village, Kalintamui Village and Galagah Hulu Village. Owever, in the other three villages of Kandang Halang Village, Pangkalan Sari Village and Benua Hanyar Village, relatively not all work is done with an orderly administration. While on the implementation factor, communication and bureaucratic structure is relatively appropriate in Cempaka Village, Kalintamui Village and Galagah Hulu Village, but still relatively not suitable at Benua Hanyar Village, Kandang Halang Village and Pangkalan Sari Village. Fund resources are sufficient but in terms of quality and quantity still need to be optimized. While the disposition, the manager is very supportive with the Village Fund but need to be more carefully considered in the appointment of bureaucrats. Keywords: implementation, management, village fund.